2001
DOI: 10.1074/jbc.m105027200
|View full text |Cite
|
Sign up to set email alerts
|

Different Roles for Basic and Aromatic Amino Acids in Conserved Region 2 of Escherichia coli ς70 in the Nucleation and Maintenance of the Single-stranded DNA Bubble in Open RNA Polymerase-Promoter Complexes

Abstract: Amino acid residues in region 2 of 70 have been shown to play an important role in the strand separation step that is necessary for formation of the functional or open RNA polymerase-promoter complex. Here we present a comparison of the roles of basic and aromatic amino acids in the accomplishment of this process, using RNA polymerase bearing alanine substitutions for both types of amino acids in region 2. We determined the effects of the substitutions on the kinetics of open complex formation, as well as on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
122
5

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(137 citation statements)
references
References 32 publications
10
122
5
Order By: Relevance
“…Substitutions of alanine for aromatic amino acids in region 2.3 of 70 were shown to adversely affect formation of open complexes at promoters (12,22). Consistent with these observations, we show that the Y430A and W433A substitutions both reduce K f by 2.5-fold and K 1 to a lesser extent ( Table 1, compare line 1 with lines 5 and 6).…”
Section: And 3)supporting
confidence: 78%
See 3 more Smart Citations
“…Substitutions of alanine for aromatic amino acids in region 2.3 of 70 were shown to adversely affect formation of open complexes at promoters (12,22). Consistent with these observations, we show that the Y430A and W433A substitutions both reduce K f by 2.5-fold and K 1 to a lesser extent ( Table 1, compare line 1 with lines 5 and 6).…”
Section: And 3)supporting
confidence: 78%
“…These values should be considered approximate because of the small changes in extents of binding detected for the slow phase over the duration of our observations (30 min). All the same, comparison of the ratios of rate constants indicates that the RF 3 formed with wt RNAP is 3-fold more stable than that containing YYW RNAP, which is qualitatively consistent with the results presented in Table 1 and elsewhere (12,22).…”
supporting
confidence: 81%
See 2 more Smart Citations
“…To elucidate the molecular procedures of base unpairing during open complex formation, altered forms of DNA (depurinated, nicked, forked, or with single-stranded gap) in the Ϫ10 region were used as templates (10,(14)(15)(16)(17)(18)(19). These studies suggested that base unpairing involves an initial distortion or localized melting event around Ϫ11 (16,20). In this paper, we provide results by using intact duplex DNA to demonstrate that the adenine residue itself at the position Ϫ11 of the nontemplate strand plays a master role in the initiation of base unpairing.…”
Section: U Nder Ordinary Physiological Conditions Transcription Inmentioning
confidence: 99%